Sorting Out Pandora’s Box: Discerning the Dynamic Roles of Liver Microenvironment in Oncolytic Virus Therapy for Hepatocellular Carcinoma - Altomonte, Jennifer; Ebert, Oliver (Frontiers in Oncology, 2014)
Oncolytic viral therapies have recently found their way into clinical application for hepatocellular carcinoma (HCC), a disease with limited treatment options and poor prognosis. Adding to the many intrinsic challenges of in vivo oncolytic viral therapy, is the complex microenvironment of the liver, which imposes unique limitations to the successful delivery and propagation of the virus. The normal liver milieu is characterized by an intricate network of hepatocytes and non-parenchymal cells including Kupffer cells, stellate cells, and sinusoidal endothelial cells, which can secrete antiviral cytokines, provide a platform for non-specific uptake, and form a barrier to efficient viral spread. In addition, NK cells are greatly enriched in the liver, contributing to the innate defense against viruses. The situation is further complicated when HCC arises in the setting of underlying hepatitis virus infection and/or hepatic cirrhosis, which occurs in more than 90% of clinical cases. These conditions pose further inhibitory effects on oncolytic virus therapy due to the presence of chronic inflammation, constitutive cytokine expression, altered hepatic blood flow, and extracellular matrix deposition. In addition, oncolytic viruses can modulate the hepatic microenvironment, resulting in a complex interplay between virus and host. The immune system undoubtedly plays a substantial role in the outcome of oncolytic virus therapy, both as an inhibitor of viral replication, and as a potent mechanism of virus-mediated tumor cell killing. This review will discuss the particular challenges of oncolytic viral therapy for HCC, as well as some potential strategies for modulating the immune system and synergizing with the hepatic microenvironment to improve therapeutic outcome.